The ironic apocalypse in the novels of Leopoldo Marechal - Cheadle, Norman, 1953- (Colección Támesis. Monografías ;, 2000)
Leopoldo Marechal has become a chosen precursor of many contemporary Argentine writers, cineastes, and intellectuals, and so his novels - universally recognized but rarely studied - demand treatment from a contemporary critical sensibility. This study departs from the line of criticism that reads Marechal as a Christian apologist, arguing instead that Marechal's 'metaphysical' novels are really metafictional, ludic exercises informed by ironic scepticism.